Efektivitas Strategi Pemasaran dalam Meningkatkan Minat Pendaftaran Siswa Baru - Putri, Devin Cumbuan; Ajeng, Rahayu Wilujeng; Septuri, Septuri (Universitas Islam Negeri Raden Intan Lampung, 2024)
This research is motivated by efforts to develop an Educational Marketing Strategy to increase the interest of new students at MIN 1 Pringsewu. The aim of this research is to find out the most effective educational marketing strategy to increase the interest of new students at MIN 1 Pringsewu. The research method used is descriptive qualitative with data collection techniques in the form of interviews, observation and documentation. Data analysis was carried out through data reduction, data presentation, drawing conclusions, and source triangulation. Data sources for this research include the Principal, Deputy Head of Student Affairs, Chair of the New Student Admissions Committee, Head of Administration, and Parents. The research results show that the educational marketing strategy implemented has succeeded in producing several findings, including: 1) Educational products that emphasize quality, curriculum excellence and extracurriculars; 2) Free pricing policy with no registration fees; 3) Strategic location that is easily accessible and close to public facilities; 4) Promotion through print and electronic media; 5) Competent Human Resources according to qualifications; 6) Physical evidence in the form of adequate facilities and documentation of school achievements; 7) The learning process uses a curriculum that has been approved by the government, supported by qualified teaching staff and adequate supporting facilities.